Assessment of Economic Losses of Road Transport Due to Unproductive Downtime at Railway Crossings - Kurhan, M. B.; Luzhytskyi, O. F.; Ivanov, R. V.; Kurhan, A. M. (Science and Transport Progress, 2025)
Purpose. Determining economic losses from unproductive downtime at railroad crossings requires a comprehensive approach. The authors aim to develop a methodology for calculating the economic losses of motor vehicles from unproductive downtime at railroad crossings with heavy traffic and to propose rational solutions regarding the feasibility of modernizing crossings. Methodology. The calculations of economic losses incurred by motor vehicles due to unproductive downtime at railroad crossings take into account the category of the crossing, the number of trains and the number of vehicles of different categories crossing the crossing during the day, as well as other factors included in the automated system «Pereizd» («Crossing»). The methodology takes into account the economic cost of time lost by passengers waiting in cars and buses in front of a closed crossing, as well as the economic cost of cargo downtime depending on the type of trucks and the type of transportation. Findings. During the study, the authors determined at which crossings and at what intensity of traffic the greatest economic losses from unproductive downtime are observed. The results obtained take into account the daily traffic intensity at the crossing: the number of trains and the number of vehicles of various categories, the category of crossings, and other factors. It was found out how the intensity of motor vehicle and rail transport, the frequency of opening barriers, and the duration of downtime for cars, buses, and trucks affect the costs and fuel consumption when engines are idling. The negative impact of unproductive downtime on the environment was assessed. Originality. The paper proposes a methodology for assessing the economic losses of motor vehicles from unproductive downtime at the busiest railroad crossings. The economic losses of motor vehicles are assessed by analyzing a number of factors related to traffic flow, downtime, fuel consumption, lost time, and environmental pollution. Practical value. The developed method makes it possible to estimate the economic losses of motor vehicles from unproductive downtime at railroad crossings, which is confirmed by examples from the operation of crossings on the routes of the regional branch «Prydniprovska Railway».